Descriptive Analysis of Risk Factors and Trends in Healthcare-Associated Infections: A 5-Year Retrospective Surveillance Study in East Java, Indonesia (2019-2023) - Aine Artalia; Elsye Maria Rosa (Jurnal Penelitian Pendidikan IPA, 2025)
Healthcare-Associated Infections (HAIs) remain a significant challenge in healthcare settings due to their impact on patient morbidity, mortality, and treatment costs. This study aimed to describe the trends and risk factors of HAIs using retrospective surveillance data from 2019–2023 at a public hospital in East Java, Indonesia. A total of 18,115 patients with invasive medical devices and 1,674 HAI cases were analyzed. Descriptive statistics, chi-square tests, and epidemiological indicators—point prevalence, incidence density, and device-associated infection rates—were used. The highest point prevalence occurred in 2021, reaching 112.02 per 1,000 patients (11.2%), with an incidence density of 3.11 per 1,000 patient-days and a device-associated infection rate of 7.94 per 1,000 device-days. These figures declined in 2023 to 77.18 per 1,000 patients (7.7%), 2.30 per 1,000 patient-days, and 6.42 per 1,000 device-days, respectively. Major risk factors included prolonged hospitalization, use of invasive devices such as catheters and ventilators, and comorbidities like diabetes mellitus and chronic diseases. The findings highlight the need for continuous monitoring, staff training, and optimized infection prevention strategies to reduce HAIs and enhance patient safety.